Beginning with biology: "Aspects of cognition" exist in the service of the brain's overall function as a resource-regulator. (11th March 2020) - Theriault, Jordan E.; Coleman, Matt; Feldman, Mallory J.; Fridman, Joseph D.; Sennesh, Eli; Barrett, Lisa Feldman; Quigley, Karen S.
Abstract: Lieder and Griffiths rightly urge that computational cognitive models be constrained by resource usage, but they should go further. The brain's primary function is to regulate resource usage. As a consequence, resource usage should not simply select among algorithmic models of "aspects of cognition." Rather, "aspects of cognition" should be understood as existing in the service of resource management.